Konotacyjne i asocjacyjne właściwości określeń identyfikujących barwy (na przykładzie nazw farb ściennych) - Graf, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The article analyses the names that define colours of interior wall paints that are currently available on the Polish market. The results of the analysis are then used to identify and discuss substantial problems that accompany unequivocal classification of these descriptions (descriptors) into a delimitatrion of the category of proper names. More detailed analyses, approaching the available linguistic material from the perspective of their marketing value and function, have made it possible to reveal the manifestations of the ritualisation of language, and to provide a typology for the most frequently used themes employed by creators of names, such as “closeness to nature” or “virtual journey” that, in the process of perception, provoke and enhance particular associations in the recipient’s consciousness.